Spatial Autocorrelation of Communes’ Income Potential in Selected Metropolitan Areas - Kozera, Agnieszka Bernadetta; Głowicka-Wołoszyn, Romana (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
A commune’s own income potential, indicative of financial self‑sufficiency, underpins the ability of its government to foster local growth. Accurate recognition of the potential levels necessary for improvement of development policies requires that, apart from considering communes’ own potential, neighbouring communes’ potential should be taken into account, especially if the neighbours are large urban centres of substantial demographic and economic capacity. This article aims to examine spatial autocorrelation of income potential of metropolitan communes of Warsaw, Poznań, Wrocław, and Cracow metro areas in 2014. The study draws on data published by the Central Statistical Office in the Local Data Bank and uses the R programme packages, such as spdep, maptools, and shapefiles for calculations.